Nuclear Phosphatidylcholine and Sphingomyelin Metabolism of Thyroid Cells Changes during Stratospheric Balloon Flight. (9th November 2009) - Albi, Elisabetta; Cataldi, Samuela; Villani, Maristella; Perrella, Giuseppina
Abstract : Nuclear sphingomyelin and phosphatidylcholine metabolism is involved in the response to ultraviolet radiation treatment in different ways related to the physiological state of cells. To evaluate the effects of low levels of radiation from the stratosphere on thyroid cells, proliferating and quiescent FRTL-5 cells were flown in a stratospheric balloon (BIRBA mission). After recovery, the activity of neutral sphingomyelinase, phosphatidylcholine-specific phospholipase C, sphingomyelin synthase, and reverse sphingomyelin synthase was assayed in purified nuclei and the nuclei-free fraction. In proliferating FRTL-5, space radiation stimulate nuclear neutral sphingomyelinase and reverse sphingomyelin synthase activity, whereas phosphatidylcholine-specific phospholipase C and sphingomyelin synthase were inhibited, thus inducing sphingomyelin degradation and phosphatidylcholine synthesis. This effect was lower in quiescent cells. The possible role of nuclear lipid metabolism in the thyroid damage induced by space radiations is discussed.